2014
DOI: 10.15666/aeer/1203_703716
|View full text |Cite
|
Sign up to set email alerts
|

Effect of disturbance on the ant community in a semiarid region of Central Mexico

Abstract: Abstract. Ants have been used as indicators of disturbííííance, because of their fast response to environmental changes. However, it is not well defined which disturbance factors are associated with specific changes on the ant community. We evaluated the effect of disturbance on the ant community in a xeric community from central Mexico. Two sites with contrasting levels of disturbance were chosen based on a quantitative index. We compared ant abundance, ant diversity and the main disturbance factors affecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…In this sense, ETL plays an important role in induction of volatiles in plants (War et al, 2011) when plants are attacked, and parasitoids or other members of the third trophic level use induced volatiles as cues to find the feeding herbivore (Kahl et al, 2000). Interestingly, ETL traps in the present work captured a high number of potential natural enemies of H. hampei (data not published), such as the ants Camponotus blandus (McClure et al, 2008); Crematogaster evallans (Boscardin et al, 2012), Pseudomyrmex gracilis (Rivas-Arancibia et al, 2014) and Brachymyrmex sp. (Cividanes 2002).…”
Section: Discussionmentioning
confidence: 67%
“…In this sense, ETL plays an important role in induction of volatiles in plants (War et al, 2011) when plants are attacked, and parasitoids or other members of the third trophic level use induced volatiles as cues to find the feeding herbivore (Kahl et al, 2000). Interestingly, ETL traps in the present work captured a high number of potential natural enemies of H. hampei (data not published), such as the ants Camponotus blandus (McClure et al, 2008); Crematogaster evallans (Boscardin et al, 2012), Pseudomyrmex gracilis (Rivas-Arancibia et al, 2014) and Brachymyrmex sp. (Cividanes 2002).…”
Section: Discussionmentioning
confidence: 67%
“…For example, when compared to conserved sites Rivas-Arancibia et al ( 2014) reported a decrease in abundance of Pheidole skwarrae, P. tepicana, Pogonomyrmex barbatus and Dorymyrmex pyramicus in sites disturbed by livestock grazing, human activities and land degradation. However, abundance of Brachymymex musculus increased in disturbed sites compared to undisturbed sites (Rivas-Arancibia et al 2014). Similarities in species richness, abundance, and composition of surface-active arthropods among the different distances from the mining sites may be because the mining sites that we sampled are like 'islands' that occur within a matrix of other anthropogenic activities.…”
Section: Discussionmentioning
confidence: 78%
“…(Grodsky & Hernandez, 2020), leaving potentially unsuitable conditions for the many desert ants that nest and forage in soil (Ikeda & des Lauriers, 2011; Nash et al, 2004). Indeed, soil texture is known to affect the distribution of desert ant species (Johnson, 1992), and soil compaction has been shown to negatively affect granivorous ants in an arid ecosystem of central Mexico (Rivas‐Arancibia et al, 2014). Although cacti and Mojave yucca ( Yucca schidigera ) remained absent from mowed areas in the facility seven years post‐construction, creosote ( Larrea tridentata ) and white bursage ( Amrbosia dumosa ) recovered to reach covers similar to those in controls (Grodsky & Hernandez, 2020).…”
Section: Discussionmentioning
confidence: 99%